Tourism village development strategy: A case study in Kaba-kaba village, Tabanan-Bali - Pantiyasa, I Wayan; Sutiarso, Moh Agus; Susanto, Budi; Kasiani, Kasiani (YAYASAN MITRA PERSADA NUSANTARA, 2023)
The objectives of this study are to determine the perception and participation of the community towards the development of Kaba-kaba tourism villages, to find out the internal and external conditions of Kaba-kaba Village, and to formulate a strategy for the development of Kaba-kaba tourism villages. The research method was carried out by collecting data on interviews, observations, documentation, and Focus Group Discussion. Data in analysis with descriptive qualitative and SWOT analysis. The results of the research are the public's perception of the development of the Kaba-kaba tourist village is generally good, but they do not understand well because socialization has never been carried out and the community will support its development. Direct community participation is only a small part, especially those who are willing to guide tourism and the provision of food and drink, indirect participation of the community in working together in cleaning the village environment. Tourism village development strategy can be divided into several aspects, including conservation and revitalization, development of tourist products, improvement of facilities and infrastructure, improvement of human resources, management of tourism village, marketing system, increase of community participation, and improvement of other facilities.